Effect of Multimodal Assessment Packages on Senior Secondary School Students' English Listening Proficiency in Ibadan Metropolis Oyo State, Nigeria. (2023)
The study determined the effect of curriculum-based multimodal technique on the listening skills proficiency among secondary school students in Ibadan metropolis. The quasi experimental design was adoptedfor this study. The instruments were Oral-based tests with reliability co-efficient of 0.89, Paper- based tests with reliability co-efficient of 0.70. A total of200 students were randomly selectedfrom public and private schools in Ibadan metropolis and were examined. Half of the students (100) are from public-based secondary schools while the remaining 50% (100) are from private schools. Analysis of variance was used in analysing the main and interaction effects of the data collected. The results revealed that there was no significant different in the overall listening skill proficiency of the students based on either of the school or test type. However, there exists a strong interaction between these independent variables. Students from public schools performed better in Oral-based test (ORT), while private school students tends to have better performance in paper- based tests (PBT). The public school students with a mean performance score of79.38%performed better than the private school students (x— 78.5%) in term of the overall average in the conducted tests Based on thefindings, the new (ORT) technique ofassessing listening skill should be adopted by teachers and all public examining bodies in Nigeria in assessing students listening proficiency